Consumer demand as a basis for formation of environmental turproduct - Tleuberdinova, A.T.; Ospanov, B.R.; Junissova A.Т. (BUKETOV BUSINESS REVIEW, 2018)
According to the majority of experts, the available natural potential of the republic and the level of development of tourism infrastructure are predetermined as the most promising type of tourism for development in the Republic of Kazakhstan at the current stage – ecological tourism. The purpose of the work is to determine the general consumer preferences of ecotourists, on the example of the developed countries of Europe and the North American continent, which are necessary for the subsequent formation of a tourist product. The paper is a theoretical-empirical study. The article clarifies the concept of «ecological tourism», its distinctive characteristics are defined. The authors conducted an excursus into the history of ecological tourism. The reasons for the growing demand for eco-tourism are explained. The authors substantiate the relevance of the development of ecological tourism in Kazakhstan. Examples are given of measures to stimulate the development of ecological tourism in Kazakhstan. The result of the work was a comparative analysis of the preferences of ecotourists from different countries and the definition of general characteristics of the demand for tourist services. The article examines the experience of foreign countries in analyzing consumer demand for ecological tourism. From the history of international tourism identified the problems that most often impede the development of ecological tourism. The authors defined measures to enhance the development of ecotourism in the country.